PENGARUH KUALITAS PRODUK DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN PADA DEUMDEE CAFE RANGKASBITUNG - Suryanisari, Pipin; Prasetyo, Andrian (The Asia Pacific Journal Of Management Studies, 2023)
This study aims to determine the effect of product quality and customer satisfaction on customer loyalty. Product Quality (X1) and Consumer Satisfaction (X2) are independent variables and Customer Loyalty (Y) is the dependent variable. The research method used in this research is quantitative method. The population used in this study were 95 customers of Cafe Deumdee Rangkasbitung. The number of samples used in this study were 95 respondents using the slovin method. The data used in this study is primary data, namely by distributing questionnaires to respondents. The scale used is the Likert scale. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple linear regression test, correlation test, determination test, t test and f test. The results of testing the first hypothesis (H1) are accepted which indicates that product quality has an effect on customer loyalty. The results of testing the second hypothesis (H2) are rejected which indicates that consumer satisfaction has no effect on customer loyalty. While the results of testing the third hypothesis (H3) are accepted which shows that Product Quality and Consumer Satisfaction have an effect on customer loyalty.